Keputusan Berinvestasi Secara Digital di Siswa Sekolah Menengah - Susanti, Eka Nana; Alimudin, Muhamad (Jurnal EMT KITA, 2025)
Investment is an activity that can be undertaken by anyone. Recently, numerous investment models have emerged in the digital world. The variety of investment models requires individuals to be cautious in selecting the right investment. For students, understanding financial literacy is crucial to avoid making poor investment decisions. This study aims to identify students' knowledge about investments and determine the influence of financial literacy on investment decision-making. The research employs a quantitative method with 91 respondents. Data analysis includes validity tests, reliability tests, simple linear regression, t-tests, and F-tests. The results of the study indicate that the partial test (t-test) yielded a t-value of 3.350, exceeding the t-table value of 1.985, with a significance level of 0.000 (3.350 > 1.985 and 0.000 < 0.05), suggesting that H0 is rejected and H1 is accepted. This indicates that financial literacy significantly influences investment decision-making. The simultaneous F-test shows that financial literacy has a positive simultaneous influence on investment decision-making, as indicated by an F-value of 13.476, exceeding the F-table value of 3.84, with a significance level of 0.000 (13.476 > 3.84 and 0.000 < 0.05). It can be concluded that financial literacy simultaneously influences investment decision-making.